Social effects of HIV disclosure, an ongoing challenge in young adults living with perinatal HIV: a qualitative study - Aurpibul, Linda; Tangmunkongvorakul, Arunrat; Detsakunathiwatchara, Chanidapa; Masurin, Supunnee; Srita, Angkana; Meeart, Patcharaporn; Chueakong, Walailak (Frontiers in Public Health, 2023)
Introduction Young adults with perinatal HIV (YAPHIV) have survived the long journey of life while living with HIV since early childhood. We explore the HIV disclosure experience and its social effects from their perspectives. Methods The qualitative study was conducted from June to November 2022 in Chiang Mai, Thailand. Data were collected through individual in-depth semi-structured interviews with 20 YAPHIV at the median age of 25 years. Content analysis was used to identify themes from the interview transcripts. Results Most participants learned their HIV status from their parents, caregivers, healthcare providers, or other people in community during their childhood. Some were disclosed later in adolescent years. HIV disclosure to others was associated with various experiences in different stages of life. While some YAPHIV decided not to disclose their HIV status to anyone, it also had social effects. Three major themes were identified: (1) positive social effects of HIV disclosure (perceived social acceptance, perceived social support); (2) negative social effects of HIV disclosure (effects on child rearing, schooling, and family relationship); and (3) HIV non-disclosure (anticipated stigma, negative effects on the quality of employment, and relationships). An emerging theme was a need for peer support mentioned by several YAPHIV as they would like to discuss with somebody and share their feelings while living with HIV. Conclusion HIV disclosure remains challenging for YAPHIV while growing up and moving toward adult milestones. Better understanding their situations and perspectives would allow healthcare providers to provide them with updated HIV knowledge, coping skills, and psychosocial support.